Feasibility and Accuracy of Automated Three-Dimensional Echocardiographic Analysis of Left Atrial Appendage for Transcatheter Closure - Pedro, Morais (2021)
Background: Procedural success of transcatheter left atrial appendage closure (LAAC) is dependent on correct device selection. Three-dimensional transesophageal echocardiography (3DTEE) is more accurate than the two-dimensional (2D) modality for evaluation of the complex anatomy of LAA. However, 3D-TEE analysis of LAA is challenging and highly expertise dependent. In this study, we sought to evaluate the feasibility and accuracy of a novel software tool for automated 3D analysis of the LAA using 3D-TEE data. Methods: The intra-procedural 3D TEE data of 158 patients who underwent LAAC were retrospectively analyzed with a novel automated LAA analysis software tool. Based on the 3D TEE data, the software semi-automatically segmented the 3D LAA structure, determined the device landing zone (LZ), and generated measurements of the LZ dimensions and the LAA length, allowing manual editing if necessary. The accuracy of LAA pre-implantation anatomic measurement reproducibility, and time for analysis of the automated software were compared against expert manual 3D analysis. The software feasibility to predict the optimal device size was directly compared to implanted models. Results: Automated 3D analysis of the LAA on 3D-TEE was feasible in all patients. There were excellent agreements between automated and manual measurements of LZ maximal diameter (bias:-0.32, LOA:-3.56; 2.92), area-derived mean diameter (bias:-0.24, LOA:-3.12, 2.64), and LAA depth (bias:0.02, LOA:-3.14; 3.18). Automated 3D analysis, with manual editing if necessary, accurately identified the implanted device size in 90.5% of patients, outperforming 2DTEE (68.9%, p<0.01). The automated software showed results competitive against the manual analysis of 3D-TEE with higher intra- and inter-observer reproducibility and allowed quicker analysis (101.9±9.3s vs. 183.5±42.7s, p<0.001) compared to manual analysis.